AKTIVITAS ANTIBAKTERI MINYAK ATSIRI KULIT JERUK PONTIANAK TERHADAP Staphylococcus aureus dan Escherichia coli - Rafika Sari; F. Nour Aulia Mustari; Sri Wahdaningsih (Majalah Obat Tradisional, 2013)
The infectious diseases can be caused by the pathogenic bacteria among Staphylococcus aureus and Escherichia coli. One of the plants that can be used as antibacterial is essential oils from Pontianak orange peels (Citrus nobilis Lour. var. microcarpa). This research aims to determine the antibacterial activity essential oils Pontianak orange peels againts the pathogenic bacteria by disc diffusion method. This research carried out by using the experimental Completely Randomized Design (CRD) Factorial and outcome data were analyzed using the program CoStat Two Way ANOVA method and continued by using LSD (Least Significant Different). The results showed that the essential oils from Pontianak orange peels contain flavonoids, saponins, and triterpenoids. The essential oils from Pontianak orange peels have antibacterial activity againts Escherichia coli and Staphylococcus aureus, where the average zone of inhibition obtained from the concentrations from 0,5; 1,5; and 2,5 mg/mL respectively are 15; 16; and 19 mm and 16,33; 18; and 21 mm. The concentration that gives the biggest inhibition zone is 2,5 mg/mL.